Effective adsorption of phosphate from aqueous solution by La-based metal–organic frameworks. Issue 107 (4th November 2016) - Liu, Hua; Guo, Weilin; Liu, Zhonghua; Li, Xianghui; Wang, Ruiqin
Abstract : In this study, lanthanide-based metal–organic frameworks (La-MOFs) were prepared by a hydrothermal method and employed for the adsorption of phosphate from water. Abstract : In this study, lanthanide-based metal–organic frameworks (La-MOFs) were prepared by a hydrothermal method and employed for the adsorption of phosphate from water. The structure and properties of La-MOFs have been verified by X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, and zeta potential measurements. Afterward, its performance as an adsorbent for phosphate removal was investigated. Experiments were performed to study the effects of various conditions on the phosphate adsorption, including adsorbent dosages, contact time and the initial pH. The results indicated that the phosphate adsorption on La-MOFs was pH-dependent. The experimental data were interpreted elaborately by different models of adsorption kinetics and isotherms. The results showed that the kinetic data fitted well to the pseudo-second-order models, indicating that the adsorption behaviors were mainly ascribed to both physisorption and chemisorption. The equilibrium data were best described by the Langmuir isotherm model with a maximum adsorption capacity of about 142.04 mg g −1 . Moreover, the adsorbed phosphate could be almost desorbed completely with NaOH solution for reusability. To summarize, La-MOFs are a promising adsorbent for the phosphate adsorption from water.